Rancang Bangun Sistem Informasi Pengelolaan Barang Untuk Usaha Kecil Menengah Berbasis Web - Raden Erwin Gunadhi Rahayu; Leni Fitriani; Gilang Adi Pratama (Jurnal Algoritma, 2026)
Small and medium enterprises (SMEs) Karya Bhakti face challenges in inventory management, such as stock calculation errors, manual recording, and limited access for owners to reports and inventory in two separate stores. To overcome these problems, this study aims to design and develop a web-based inventory management information system that can be accessed online by owners and employees. This study uses the Rational Unified Process (RUP) method, which consists of four stages: Inception, Elaboration, Construction, and Transition. The system design was carried out using Unified Modeling Language (UML) with four main diagrams: use case, activity, sequence, and class diagrams. The system was implemented using the PHP programming language and the Laravel framework. The results of this study indicate that this system can facilitate the process of managing incoming and outgoing goods, migrating stock between stores, and compiling monthly reports. The main contribution of this study is the development of a web-based goods management system that supports multi-users and remote access, which can significantly improve the operational efficiency of SMEs.